2020
DOI: 10.1016/j.cegh.2019.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Cystic Echinococcosis and related risk factors for infection among children in a rural community in Fars Province, Southern Iran

Abstract: Background: Cystic Echinococcosis (CE) or hydatid cyst is one of the most common diseases between humans and livestock that is caused by the larval stage of Echinococcus granulosus. The disease is a major health and also economic concern in Iran. Most of the studies on CE in different areas of Iran have been conducted in adults and there is little information about the prevalence of the disease in children. Methods: This cross-sectional study was conducted to find out the seroprevalence of hydatid cyst in chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 21 publications
4
18
1
Order By: Relevance
“…CE is considered a neglected disease with significant mortality and morbidity in most of the developing countries [1,4,5 ]. The disease is a major health and economic challenges in the Middle East countries, including Iran where about 1% of all hospital surgeries are accounted for this disease [1,4,5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…CE is considered a neglected disease with significant mortality and morbidity in most of the developing countries [1,4,5 ]. The disease is a major health and economic challenges in the Middle East countries, including Iran where about 1% of all hospital surgeries are accounted for this disease [1,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…CE is considered a neglected disease with significant mortality and morbidity in most of the developing countries [1,4,5 ]. The disease is a major health and economic challenges in the Middle East countries, including Iran where about 1% of all hospital surgeries are accounted for this disease [1,4,5]. A recent systematic review and meta-analysis reported the overall seroprevalence of CE in Iran to be 4.2% in human hosts, with the highest seroprevalence (5.8%) in the South and the least (2.2%) in the central areas of the country [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Several studies have been focused on cystic echinococcosis in children and it has been suggested that in areas where the prevalence of hydatid cyst in adults is high, this prevalence is also high in children. [7][8][9] However, published researches regarding the pattern and characteristics of human CE involvement in adults are rare. The current study aimed to explore the trend and features as well as risk and exposure factors of CE in adults living in an endemic area in Morocco.…”
Section: Introductionmentioning
confidence: 99%
“…CE is considered a neglected disease with significant mortality and morbidity in most of the developing countries [1]. The disease is a major health and economic challenge in the Middle East countries, including Iran where about 1% of all hospital surgeries are accounted for this disease [1][2][3][4][5].…”
mentioning
confidence: 99%